The effect of climate change on electricity planning - Ferreira, Paula M. T. (2015)
The literature is vast in what regards the relationship between climate change (CC) and energy, especially in the sense of pointing this sector as an inducer of greenhouse gases (GHG) and demonstrating the importance of Renewable Energy Sources (RES) in mitigating these impacts. The relationships in the opposite direction, i.e. the way how CC could affect energy systems, are now being recognized as increasingly important by some international organizations and authors. This is precisely the focus of this paper, aiming to demonstrate how CC can affect RES and future electricity scenarios. The work addresses the particular case of Portugal and departed from the assessment of the impact of CC upon parameters of interest to hydro, wind and solar power production, according to international studies. This information was used as input of an optimization model for a long term power planning, resulting in the proposal of trajectories of the Portuguese electricity system under different CC assumptions.